Ruptur Tendon Achilles: Tinjauan Pustaka - Rani Himayani; Helmi Ismunandar; Ranti ayu puspita Alwi (CV. Jasa Sukses Abadi, 2021)
The Achilles tendon (AT) is the most frequently ruptured tendon in the human body but its etiology is poorly understood. Achilles tendon rupture (44% to 83%) occurs during sports activities, intrinsic structural, biochemical, and biomechanical changes associated with aging. The two main explanations for mechanism are degenerative and mechanical theories. The diagnosis of AT rupture is based on a history of such a sudden feeling of pain in the heel, sometimes accompanied by a pounding sound during activity. Specific physical examinations that can be done are the Simmonds or Thompson squeezed test, O'Brien's test, the matles or knee flexion test, and the Copeland test or sphygmomanometer. The diagnosis can be made by a good history and physical examination. Imaging is usually not required, as a diagnosis can be made clinically. Ultrasound or magnetic resonance imaging (MRI) can help if the diagnosis is not clear (partial rupture or tendonopathy). Non-operative and operative management may be options. The initial management of Achilles tendon rupture is rest, elevation, pain control, and functional support. For most patients with Achilles tendon rupture, the prognosis is very good. However, in some non-athletic patients, there may be some residual deficits such as reduced range of motion. No matter which method is used to treat tendon ruptures, participating in exercises is very important.